Analysis of The Role of Leadership Style Work Satisfaction and Work Motivation on Teacher Performance - Sudadi, Sudadi; Lahiya , Arkam; Rijal , Syamsu; Mustafa , Fahrina; Sandra Lumingkewas , Cindy (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study aims to clarify how leadership style, motivation, and job satisfaction affect teacher effectiveness. Research of this kind is quantitative. The participants in this study were all educators. 50 respondents are used for the saturation sampling-based data retrieval process. SPSS was used to obtain data for this study through multiple regression analysis on documentation and questionnaires. The significance level of 0.000 < 0.05 and the adjusted r-square of 0.43 of the study's findings, which show a simultaneous and substantial relationship between leadership style, motivation, and work satisfaction and teacher performance, respectively. The remainder is explained by factors not related to this study. Partially, work happiness, motivation, and leadership style all have a substantial impact on teachers' performance. These factors also all have a significant impact on teachers' performance.